2018
DOI: 10.1002/jcph.1349
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Study and Individual Dose Adjustments of High‐Dose Methotrexate in Chinese Pediatric Patients With Acute Lymphoblastic Leukemia or Osteosarcoma

Abstract: High‐dose methotrexate (>0.5 g/m2) is among the first‐line chemotherapeutic agents used in treating acute lymphoblastic leukemia (ALL) and osteosarcoma in children. Despite rapid hydration, leucovorin rescue, and routine therapeutic drug monitoring, severe toxicity is not uncommon. This study aimed at developing population pharmacokinetic (popPK) models of high‐dose methotrexate for ALL and osteosarcoma and demonstrating the possibility and convenience of popPK model–based individual dose optimization using R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
4
30
1
Order By: Relevance
“…The final model demonstrated that the MTX clearance estimate in a typical child with a body weight of 19 kg was 6.9 L/h. This value was similar to those reported previously: 8.8 L/h in 79 ALL pediatric patients with an average body weight of 25.3 kg by Piard et al (Piard et al, 2007), 7.87 L/h in 64 ALL pediatric patients with an average body weight of 25 kg (Faganel et al, 2011), and 7.73 L/h in 36 ALL pediatric patients with an average body weight of 23.4 kg (Hui et al, 2019). The central distribution of volume estimate in current study was 20.7 L, which was similar to that reported by a previous study (16.7 L) involving 64 pediatric patients with ALL/ML (Faganel et al, 2011) and somewhat higher than that reported by another pediatric study (9.3 L for a typical child with body weight of 20 kg) (Aumente et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The final model demonstrated that the MTX clearance estimate in a typical child with a body weight of 19 kg was 6.9 L/h. This value was similar to those reported previously: 8.8 L/h in 79 ALL pediatric patients with an average body weight of 25.3 kg by Piard et al (Piard et al, 2007), 7.87 L/h in 64 ALL pediatric patients with an average body weight of 25 kg (Faganel et al, 2011), and 7.73 L/h in 36 ALL pediatric patients with an average body weight of 23.4 kg (Hui et al, 2019). The central distribution of volume estimate in current study was 20.7 L, which was similar to that reported by a previous study (16.7 L) involving 64 pediatric patients with ALL/ML (Faganel et al, 2011) and somewhat higher than that reported by another pediatric study (9.3 L for a typical child with body weight of 20 kg) (Aumente et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…12,14,16 Therefore, eGFR (estimated glomerular filtration rate), Ccr, and Scr have been identified as important factors affecting MTX pharmacokinetics in various population pharmacokinetic analyses. 12,14,28,29 Scr and eGFR were also significant in the present study; however, the most important factor was Ccr. Therefore, Ccr based on Scr influences MTX pharmacokinetics in PCNSL patients.…”
Section: Discussionsupporting
confidence: 52%
“…The folate analogue MTX acts as an antineoplastic agent via competitive inhibition of dihydrofolate dehydrogenase, resulting in depletion of purines and thymidylate leading to impairment of DNA synthesis [ 2 , 3 ]. The drug can be administered via multiple routes of administrations and has a wide variation in dosing regimens including low (< 50 mg/m 2 ), intermediate (50–500 mg/m 2 ) and high (> 500 mg/m 2 ) dose regimens [ 1 , 4 ]. The pronounced inter-individual variability (IIV) of PK and toxicity of MTX [ 5 7 ] renders individualization of dosing regimens difficult.…”
Section: Introductionmentioning
confidence: 99%